New Approaches to the Differential Diagnosis of Functional Bowel Diseases in Children - O.G. Shadrin; O.M. Platonova; O.O. Starets (Zaslavsky O.Yu., 2013)
The study was aimed to assess the prevalence of functional bowel diseases (FBD) among children and the adequacy of the use of the Rome criteria in pediatric practices in Ukraine. It is shown that at the prehospital stage there are observed numerous cases of improper use of diagnostic criteria for FBD. It is proved that Rome III criteria in pediatrics allow to accurately diagnose FBD in older children, although a large group of patients with FBD of unknown origin requires development of new approaches to diagnosis. And implementation of the Rome criteria by specialists of the primary and secondary level of medical care is not active enough, 50 % of FBD cases at the outpatient stage is not diagnosed. We discuss the need to develop algorithms for predicting FBD in childhood to improve the detection level of functional pathology of the gastrointestinal tract.